Changes in health behaviors associated with weight gain by weight classification during the COVID-19 pandemic. - Rupp, Kristie; Friel, Ciarán P (American journal of health promotion : AJHP, 2021)
Purpose: To determine whether perceived changes (i.e. perception of engagement during the pandemic relative to pre-pandemic) in specific health behaviors differ by weight status (i.e. healthy weight, overweight, obese). Design: Cross-sectional. Recruitment took place between June-August 2020, via social media posts and Qualtrics online panels. Setting: Participants completed the survey online through the Qualtrics platform. Sample: Analyses included N = 502 participants (≥18 years); 45.2% healthy weight (n = 227), 28.5% overweight (n = 143), and 26.3% obese (n = 132). Measures: Study-specific survey items included questions about demographics and perceived changes in health behaviors. Analysis: Logistic regression models, adjusted for age, race, ethnicity, gender, education, and COVID-19 diagnosis, assessed the odds of perceiving changes in health behaviors considered a risk for weight gain. Results: Participants with obesity, but not overweight, were significantly more likely to report deleterious changes to health behaviors compared to healthy weight peers, including: (1) decreased fruit/vegetable consumption [adjusted odds ratio (AOR) = 1.92; 95% confidence interval (CI): (1.13, 3.26)]; (2) increased processed food consumption [AOR = 1.85; 95%CI: (1.15, 3.00)]; (3) increased caloric intake [AOR = 1.66; 95% CI: (1.06, 2.61)]; (4) decreased physical activity [AOR = 2.07; 95%CI: (1.31, 3.28)]; and (5) deterioration in sleep quality [AOR = 2.07; 95%CI: (1.32, 3.25)]. Conclusion: Our findings suggest that adults with obesity may be at greater risk for unhealthy behaviors during a period of prolonged social distancing, potentially exacerbating the obesity epidemic. © The Author(s) 2021.
4 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34098761/ ; https://europepmc.org/article/MED/34098761 ; http://journals.sagepub.com/doi/10.1177/08901171211022958 ; https://www.ncbi.nlm.nih.gov/pubmed/34098761 ;
Keywords: COVID-19; COVID-19 Testing; Cross-Sectional Studies; Health Behavior; Humans; Pandemics; SARS-CoV-2; Sleep Quality; Weight Gain; body weight gain; cross-sectional study; dept.hms; health behavior; human; pandemic; peer-reviewed; sleep quality

Athletic training employment in secondary schools by geographic setting and school size within the United States. - Suzuki-Yamanaka, Miwako; Huggins, Robert A.; Armstrong, Kirk J.; Coleman, Kelly A.; Casa, Douglas J.; Kaneoka, Koji (Journal of athletic training, 2021)
Context: The Athletic Training Locations and Services (ATLAS) Annual Report suggested that athletic trainer (AT) employment status differed based on geographic locale. However, the influence of geographic locale and school size on AT employment is unknown. Objective: To determine if differences existed in the odds of having AT services by locale for public and private schools and by student enrollment for public schools. Design: Cross-sectional study. Setting: Public and private secondary schools with athletics programs. Patients or Other Participants: Data from 20 078 US public and private secondary schools were obtained. Main Outcome Measures(s): Data were collected by the ATLAS Project. Athletic trainer employment status, locale (city, suburban, town, or rural) for public and private schools, and school size category (large, moderate, medium, or small) only for public schools were obtained. The employment status of ATs was examined for each category using odds ratios. Logistic regression analysis produced a prediction model. Results: Of the 19 918 public and private schools with available AT employment status and locale, suburban schools had the highest access to AT services (80.1%) with increased odds compared with rural schools (odds ratio = 3.55 [95% CI = 3.28, 3.85]). Of 15 850 public schools with known AT employment status and student enrollment, large schools had the highest rate of AT services (92.1%) with nearly 18.5 times greater odds (odds ratio = 18.49 [95% CI = 16.20, 21.08]) versus small schools. The logistic model demonstrated that the odds of access to an AT increased by 2.883 times as the school size went up by 1 category. Conclusions: Nationally, suburban schools and large public schools had the greatest access to AT services compared with schools that were in more remote areas and with lower student enrollment. These findings elucidate the geographic locales and student enrollment levels with the highest prevalence of AT services. Ó by the National Athletic Trainers’ Association, Inc
1 citations (Crossref) [2023-10-31] https://www.ncbi.nlm.nih.gov/pubmed/33480996 ; https://pubmed.ncbi.nlm.nih.gov/33480996/ ; https://meridian.allenpress.com/jat/article/56/9/1010/451538/Athletic-Training-Employment-in-US-Secondary ; https://europepmc.org/article/MED/33480996
Keywords: adult; article; athletic trainer; athletics; controlled study; cross-sectional study; dept.hms; employment status; female; high school; human; male; outcome assessment; peer-reviewed; prediction; prevalence; training

Flu vaccinations: College campus not making the grade. A study of influenza vaccination at an urban public university. - Kreiger, Joan E; Zigmont, Victoria A.; Michalski, Carrie D; Borgognone, Kristen S (Journal of American college health : J of ACH, 2021)
Objective: Even healthy college students are vulnerable to severe complications associated with seasonal influenza (flu). Despite national directives to increase influenza vaccination compliance, college campuses remain woefully below national goals. This study aimed to identify factors correlated with the decision to voluntarily receive an influenza vaccine. Additionally, students’ reasons for non-vaccination were also examined. Participants: 1021 undergraduate students across four professional schools. Methods: A representative cross-sectional survey was conducted at a public, urban university. Results: The survey measured self-reported influenza vaccination: an overall influenza vaccination rate of 38% was identified. Student characteristics associated with increased influenza vaccination included students’ enrollment in academic health disciplines; being female; human papillomavirus (HPV) vaccination; and no marijuana use in the last month. Barriers to influenza vaccination included contraindications, mistrust issues, and personal reasons. Conclusion: Universities that can identify facilitators and barriers to voluntary influenza vaccination can assist with program initiatives to improve influenza vaccination compliance rates. © 2021 Taylor & Francis Group, LLC.
2 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34670106/
Keywords: dept.hms; dept.nur; dept.pch; peer-reviewed

Establishing a global standard for wearable devices in sport and exercise medicine: Perspectives from academic and industry stakeholders - Ash, Garrett I.; Stults-Kolehmainen, Matthew; Busa, Michael A.; Gaffey, Allison E.; Angeloudis, Konstantinos; Muniz-Pardos, Borja; Gregory, Robert; Huggins, Robert A.; Redeker, Nancy S.; Weinzimer, Stuart A.; Grieco, Lauren A.; Lyden, Kate; et al. (Sports medicine (Auckland, N.Z.), 2021)
Millions of consumer sport and fitness wearables (CSFWs) are used worldwide, and millions of datapoints are generated by each device. Moreover, these numbers are rapidly growing, and they contain a heterogeneity of devices, data types, and contexts for data collection. Companies and consumers would benefit from guiding standards on device quality and data formats. To address this growing need, we convened a virtual panel of industry and academic stakeholders, and this manuscript summarizes the outcomes of the discussion. Our objectives were to identify (1) key facilitators of and barriers to participation by CSFW manufacturers in guiding standards and (2) stakeholder priorities. The venues were the Yale Center for Biomedical Data Science Digital Health Monthly Seminar Series (62 participants) and the New England Chapter of the American College of Sports Medicine Annual Meeting (59 participants). In the discussion, stakeholders outlined both facilitators of (e.g., commercial return on investment in device quality, lucrative research partnerships, and transparent and multilevel evaluation of device quality) and barriers (e.g., competitive advantage conflict, lack of flexibility in previously developed devices) to participation in guiding standards. There was general agreement to adopt Keadle et al.’s standard pathway for testing devices (i.e., benchtop, laboratory, field-based, implementation) without consensus on the prioritization of these steps. Overall, there was enthusiasm not to add prescriptive or regulatory steps, but instead create a networking hub that connects companies to consumers and researchers for flexible guidance navigating the heterogeneity, multi-tiered development, dynamicity, and nebulousness of the CSFW field. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
9 citations (Crossref) [2023-10-31] https://waseda.pure.elsevier.com/en/publications/establishing-a-global-standard-for-wearable-devices-in-sport-and- ; https://repository.up.ac.za/handle/2263/81930?show=full ; https://www.ncbi.nlm.nih.gov/pubmed/34468950 ; https://researchportal.northumbria.ac.uk/en/publications/establishing-a-global-standard-for-wearable-devices-in-sport-and- ; https://pubmed.ncbi.nlm.nih.gov/34468950/ ; https://link.springer.com/article/10.1007/s40279-021-01543-5
Keywords: Consensus; Exercise; Humans; Sports; Sports Medicine; United States; Wearable Electronic Devices; adult; article; consensus; consumer; data science; dept.hms; electronic device; exercise; female; human; human experiment; investment; major clinical study; male; sport; sports medicine

Tell Me What You See: An Arts-Based Health Education Program for Youth. - Edmondson, Bonnie (Health Promotion Practice, 2021)
A cross-sector collaboration among a community-based organization, a prison arts program, and state departments of Public Health, Education, and Correction was established to address critical health education prevention efforts for at-risk high school-aged youth. The Tell Me What You See initiative utilizes artwork and poetry created by incarcerated youth to promote sexually transmitted disease (STD), HIV, and hepatitis prevention with students in public high schools and juvenile justice facilities. This innovative intervention integrates functional health knowledge and skills-based education through an art-based interdisciplinary approach reaching various populations of youth in multiple settings across a state. Evaluation results indicated that the materials effectively engage youth and open up a critical dialogue among peers and adults by addressing the role personal behavior can have in the prevention of STDs, hepatitis, and HIV. Lessons learned and recommendations are provided., (C)2021Sage Publications
1 citations (Crossref) [2023-10-31] Place: (C)2021Sage Publications
Keywords: Adolescent; Adult; Child; Educational Status; HIV/AIDS; Health Education; Health Promotion; Humans; STDs; Schools; Sexually Transmitted Diseases; adolescent; adolescent health; adult; arts; arts in public health; arts-based education; behavior change; child; community organization; creative arts; dept.hms; educational status; health education; health promotion; hepatitis; human; incarcerated youth; juvenile justice; partnerships; peer-reviewed; public health; school; school health; sexually transmitted disease

Physical activity participation, flourishing and academic engagement in adolescents with obesity. - McCoy, Stephanie; Rupp, Kristie (Pediatric Obesity, 2021)
Background: Adolescents with obesity are less likely to flourish and be academically engaged in comparison to their healthy weight peers. However, it is unknown how participation in physical activity influences flourishing and academic engagement in adolescents with obesity. The current study examined engagement in varying levels of physical activity and the likelihood of flourishing and academic engagement in adolescents with obesity. Methods: Analyses included 26 764 adolescents, ages 10–17 years, from the parent-reported, combined 2016–2017 National Survey of Children's Health. Participants were grouped by physical activity levels (none, low, moderate, daily). Outcome variables included flourishing (finishing tasks, staying calm when faced with a challenge and showing interest in new things) and academic engagement (completing all required homework and caring about doing well in school). Logistic regression models, adjusted for age, sex, race, household income, highest level of education in the household, behavioural conduct problems and depression assessed the likelihood of each outcome comparing physical activity levels among adolescents with obesity. Results: Adolescents with obesity who participated in any amount of physical activity (low, moderate and daily) or sports had significantly greater likelihood of flourishing and academic engagement compared those that did not engage in any physical activity (p's ¡ 0.05). Conclusions: Participation in even low amounts of physical activity or participation in sports increases the likelihood of flourishing and academic engagement in adolescents with obesity, which expands on previous findings that adolescents with obesity are less likely to flourish and be academically engaged in comparison to their healthy weight peers. © 2021 World Obesity Federation
5 citations (Crossref) [2023-10-31] Place: (C) 2021 International Association for the Study of Obesity
Keywords: Adolescent; Child; Exercise; Health Status; Humans; Pediatric Obesity; Schools; adolescence; adolescent; child; childhood obesity; dept.hms; exercise; flourishing; health status; human; obesity; peer-reviewed; physical activity; school

A PEP grant’s influence on change in a school district: One year post funding - Egan, Cate A.; Abel-Berei, Catherine P.; Karp, Grace Goc (Evaluation and program planning, 2021)
This study examined teachers' and administrators' perceptions of the institutionalization phase of the Carol M. White Physical Education for Progress (PEP) grant. A qualitative exploratory single case study (Yin, 2014) was utilized to examine the elements of the PEP grant that sustained or did not sustain after its conclusion, along with elements that were institutionalized and influences on this process. The findings were represented in the following three themes: (a) positive shifts, (b) backsliding, and (c) new directions, each with their own subthemes. Positive shifts includes sub-themes: (a) philosophy, (b) instruction, assessment and curriculum, (c) collaboration, and (d) respect. Backsliding includes sub-themes: (a) wellness team functioning, (b) the loss of PD and collaboration time, and (c) reduced data collection. New directions includes sub-themes: (a) mastery learning, (b) during school physical activity, (c) stress, and (d) administrative support. The factors that were institutionalized were quality physical education leadership roles, change in teachers' philosophies that influenced their instruction and assessment, and garnered administrative support. These elements were embedded into the physical education program and the school so much so that principals now expect the same type of programming from any new hire. Copyright © 2021 Elsevier Ltd. All rights reserved.
1 citations (Crossref) [2023-10-31]
Keywords: administration; administrative personnel; article; curriculum; dept.hms; funding; health education; human; human experiment; institutional framework; institutionalization; leadership; learning; peer-reviewed; perception; philosophy; physical activity; physical education; physiological stress; primary education; single-case study; student; teacher; teaching

Current activities centered on healthy living and recommendations for the future: A position statement from the HL-PIVOT network - Arena, Ross; Myers, Jonathan; Kaminsky, Leonard A.; Williams, Mark A.; Sabbahi, Ahmad; Popovic, Dejana; Axtell, Robert S.; Faghy, Mark A.; Hills, Andrew P.; Olivares, Silvia Lizett Olivares; Lopez, Mildred; Pronk, Nicolaas P.; et al. (Current Problems in Cardiology, 2021)
We continue to increase our cognizance and recognition of the importance of healthy living (HL) behaviors and HL medicine (HLM) to prevent and treat chronic disease. The continually unfolding events precipitated by the coronavirus disease 2019 (COVID-19) pandemic have further highlighted the importance of HL behaviors, as indicated by the characteristics of those who have been hospitalized and died from this viral infection. There has already been recognition that leading a healthy lifestyle, prior to the COVID-19 pandemic, may have a substantial protective effect in those who become infected with the virus. Now more than ever, HL behaviors and HLM are essential and must be promoted with a renewed vigor across the globe. In response to the rapidly evolving world since the beginning of the COVID-19 pandemic, and the clear need to change lifestyle behaviors to promote human resilience and quality of life, the HL for Pandemic Event Protection (HL-PIVOT) network was established. The 4 major areas of focus for the network are: (1) knowledge discovery and dissemination; (2) education; (3) policy; (4) implementation. This HL-PIVOT network position statement provides a current synopsis of the major focus areas of the network, including leading research in the field of HL behaviors and HLM, examples of best practices in education, policy, and implementation, and recommendations for the future. © 2021 Elsevier Inc.
10 citations (Crossref) [2023-10-31] Type: Review tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103372602
Keywords: Biomedical Research; COVID-19; Cardiorespiratory Fitness; Chronic Disease; Diabetes Mellitus; Diet; Exercise; Health Education; Health Policy; Healthy; Healthy Lifestyle; Humans; Implementation Science; Information Dissemination; Obesity; Patient Education as Topic; Quality of Life; Review; Risk Reduction Behavior; SARS-CoV-2; Sedentary Behavior; Smoking Cessation; Type 2; body mass; cardiorespiratory fitness; chronic disease; coronavirus disease 2019; dept.hms; education; epidemiology; exercise; health; health behavior; health care personnel; health care planning; health care policy; health education; health promotion; healthy diet; healthy lifestyle; healthy living medicine; human; information dissemination; knowledge; knowledge discovery; law; lifestyle; medical research; medicine; non insulin dependent diabetes mellitus; nutrition; obesity; pandemic; patient education; peer-reviewed; physical activity; psychological resilience; quality of life; risk reduction; sedentary lifestyle; sleep; smoking cessation; syndemic; unhealthy lifestyle behavior

Stakeholders’ perspectives on the effects of a PEP grant on a district-wide CSPAP - Abel-Berei, Catherine P.; Karp, Grace Goc; Fennell, Marcis; Drake, Elisa M.; Olsen, Simon (Journal of Teaching in Physical Education, 2021)
A Comprehensive School Physical Activity Program (CSPAP) can help children be physically active for 60 min/day. Physical Education for Progress grants provided opportunities to improve physical education and physical activity programming. Purpose: This study explored stakeholders' perspectives on the effects of a Physical Education for Progress grant on a district-wide CSPAP. Method: Stakeholders included physical educators (n = 10; K-12), administrators (n = 6), and one superintendent. Individual, semistructured interviews were used to examine how the grant affected stakeholders' perspectives of the CSPAP. Results: The grant affected the CSPAP by providing (a) opportunities for professional development, (b) opportunities to establish a K-12 curriculum map, and (c) access to equipment and resources. Discussion: Framed in social ecological theory, intrapersonal, interpersonal, institutional, and community levels were influenced by the grant. Interactions between levels enabled changes in all CSPAP components, especially quality PE. Conclusion: A Physical Education for Progress grant is a successful mechanism to enhance a district-wide CSPAP. © 2021 Human Kinetics, Inc.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85099226945
Keywords: dept.hms; peer-reviewed